2001
DOI: 10.1007/s004670100030
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyolysis and acute renal failure in children

Abstract: Acute renal failure (ARF) is an important complication of rhabdomyolysis. However, the contributing factors to the development of ARF in children with rhabdomyolysis remain obscure. The aim of this study was to clarify the factors contributing to the development of ARF in children with rhabdomyolysis. This is a retrospective review of the clinical characteristics, laboratory data, pediatric risk of mortality (PRISM) scores, the occurrence of systemic inflammatory response syndrome (SIRS) criteria, and the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
1
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 21 publications
0
42
1
2
Order By: Relevance
“…In 42 of the 52 studies that reported sex, there were more male (71%) than female patients. Most of the studies (n ϭ 46) were in the adult population; 6 studies focused on the pediatric population (13,15,34,41,51,61 ). ARF attributed to rhabdomyolysis presented in 35% of the adults and 20% of the children.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 42 of the 52 studies that reported sex, there were more male (71%) than female patients. Most of the studies (n ϭ 46) were in the adult population; 6 studies focused on the pediatric population (13,15,34,41,51,61 ). ARF attributed to rhabdomyolysis presented in 35% of the adults and 20% of the children.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Serum creatine kinase (CK), also increased in rhabdomyolysis, was measured in 38 studies (11, 13-28, 30 -34, 36 -38, 40 -45, 47, 52, 56, 57, 61-63 ), and of these, only 4 had extractable data comparing uMb with CK (45,47,51,59 ). Serum myoglobin was also measured in addition to urine myoglobin in 11 studies (19,20,23,31,40,41,43,44,46,59,61 ), but only 1 study had extractable data for a contingency table (59 ).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors for acute kidney injury during an episode of rhabdomyolysis n children include dehydration, the serum concentration of myoglobin, the presence of other organ failure, and the presence of the systemic Clinical Evaluation of Acute Kidney Injury in Children inflammatory response syndrome (61). The mechanisms of injury is complex but may be related to vasoconstriction, precipitation of the pigments in the tubular lumen and/or heme-protein induced oxidant stress (62,63). If the rhabdomyolysis is a result of tissue injury with substantial third space fluid losses as occurs in a crush injury, rapid fluid resuscitation can prevent or limit the renal injury.…”
Section: Endogenous Toxin Induced Akimentioning
confidence: 98%
“…Hemolysis and rhabdomyolysis from any cause can result in sufficient hemoglobinuria or myoglobinuria to induce tubular injury and precipitate acute kidney injury (62,63). Risk factors for acute kidney injury during an episode of rhabdomyolysis n children include dehydration, the serum concentration of myoglobin, the presence of other organ failure, and the presence of the systemic Clinical Evaluation of Acute Kidney Injury in Children inflammatory response syndrome (61).…”
Section: Endogenous Toxin Induced Akimentioning
confidence: 99%